Wordplay on Malangan T-shirt: A Linguistic Resource for Language Education - Efendy, A. Gusti (Universitas Maritim Raja Ali Haji (UMRAH), 2025)
This study delves into the linguistic ingenuity of Malangan T-shirt wordplay, a unique form of cultural expression deeply intertwined with the local identity of Malang, Indonesia. Through a comprehensive analysis of 100 T-shirt designs which were obtained from local distros and a football event in Malang, we identified a rich tapestry of wordplay techniques, including malapropisms, ambiguity, slang, and visual manipulations such as logo modifications and artistic discourse. These linguistic devices playfully subvert language norms, crafting humorous and thought-provoking messages that resonate with local audiences and challenge conventional linguistic conventions. Our research underscores the pedagogical potential of Malangan T-shirt wordplay, demonstrating its ability to enhance language education, foster cultural understanding, and cultivate critical thinking skills of language class students. By incorporating these linguistic artifacts into language instruction, educators have mote inspiration to create engaging and culturally relevant learning experiences that transcend traditional classroom approaches and promote a deeper appreciation of language and culture.